Credit Growth and the Effectiveness of Reserve Requirements and Other Macroprudential Instruments in Latin America. (IMF Working Papers; Working Paper ;, 2012)
Over the past decade policy makers in Latin America have adopted a number of macroprudential instruments to manage the procyclicality of bank credit dynamics to the private sector and contain systemic risk. Reserve requirements, in particular, have been actively employed. Despite their widespread use, little is known about their effectiveness and how they interact with monetary policy. In this paper, we examine the role of reserve requirements and other macroprudential instruments and report new cross-country evidence on how they influence real private bank credit growth. Our results show that these instruments have a moderate and transitory effect and play a complementary role to monetary policy.